Toxicological and Biochemical Analyses Demonstrate the Absence of Lethal or Sublethal Effects of cry1C- or cry2A-Expressing Bt Rice on the Collembolan Folsomia candida - Yang, Yan; Zhang, Bing; Zhou, Xiang; Romeis, Jörg; Peng, Yufa; Li, Yunhe (Frontiers in Plant Science, 2018)
Assessing the potential effects of insect-resistant genetically engineered (GE) plants on collembolans is important because these common soil arthropods may be exposed to insecticidal proteins produced in GE plants by ingestion of crop pollen, plant residues, or root exudates. Laboratory studies were conducted to evaluate the potential effects of two Bt-rice lines expressing Cry1C and Cry2A in pollen and leaves and of their non-Bt conventional isolines on the fitness of the collembolan Folsomia candida and on the activities of its antioxidant-related enzymes, superoxide dismutase and peroxidase, and of its detoxification-related enzymes, glutathione reductase and glutathione s-transferase. Survival, development, reproduction, and the intrinsic rate of increase (rm) were not significantly reduced when F. candida fed on the Bt rice pollen or leaf powder than on the non-Bt rice materials; these parameters, however, were significantly reduced when F. candida fed on non-Bt rice pollen or non-Bt leaf-based diets containing the protease inhibitor E-64 at 75 µg/g. The activities of the antioxidant-related and detoxification-related enzymes in F. candida were not significantly affected when F. candida fed on the Bt rice materials, but were significantly increased when F. candida fed on the non-Bt rice materials containing E-64. The results demonstrate that Cry1C and Cry2A are not toxic to F. candida, and also indicate the absence of unintended effects on the collembolan caused by any change in plant tissue nutritional composition due to foreign gene transformation.